Criticism of Ruhollah Rahimi's Translation of the Novel "Under the Feet of Mothers" based on the Poetics Approach of the Translation by Henri Meschonnic in 1972 - Abbas Ganjali; Sayed Mahdi Nouri keyzghani; Masoud Salmani Haghighi (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2023)
Today, translation theorists have taken a big step in the development of translation criticism methods by presenting their works and theories and have provided translators with the necessary platform to provide the desired translation. One of the theoreticians of this field is Henri Meschonnic. Translation poetics in the concept that is considered in this discussion, according to Meschonnic, is a kind of theory of text translation. Poetics deals with linguistic structure issues just as painting deals with image structures; because linguistics is the general knowledge of language structures. The poetics approach of Meschonnic’s translation consists of concepts such as transparency and centripetalism, empirical application and theoretical application, and inter-poetics relationships. In this essay, relying on the descriptive-analytical method, the Persian translation of Ruhollah Rahimi's novel "Under the Feet of Mothers" with the title "Behesht-e Maman Ghaizah" is reviewed based on the poetics approach of artistic translation by Meschonnic. The result of the research shows that the translator has used literary devices such as metonymy and non-metonymy, which have the same aesthetic effect in the source and target text, in the field of inter-poetics relations. The language of the translated text is embedded in accordance with the norms of the Meschonnic’s poetics approach and the target text, and the translator has tried to show the cultural signs of the language and ideological approach to the reader by providing an acceptable translation.Keywords: Translation Criticism, Meschonnic’s Translation Poetics, The Novel "Under the Feet of Mothers", Ruhollah Rahimi.IntroductionCriticism of translation as a linguistic and intellectual activity, although in a traditional form, has existed in parallel with translation, and sometimes the translators themselves or even the authors have measured their work and that of others with the standards of their times. Criticism of literary translation in the 20th century has taken a more scientific and methodical direction after the works of Antoine Berman on the translation of prose, Henri Meschonnic and Effim Etkind on the translation of poetry (Ahmadi, 2015: 11). For sure, it is wrong to limit the criticism of literary translation to certain people. All schools of translation criticism, even those that did not speak directly about literature or are not from this field, have concepts and tools that are effective in translation criticism, such as the theory of comparative stylistics of Vienna and Darbelneh, which has a linguistic watershed, or the function-oriented theory of Katharina Reiss's translation criticism, or the interpretative theory of the Paris school (Danica Selekovitch-Marian Lederer) or the discourse theory of Jean Delisle.Due to the fact that many novels have been translated from Arabic to Persian, it is felt necessary to make the translation process more scientific by criticizing the translation and evaluating the quality of the translation based on specific principles and elements. In order to prevent weakness and defects in translation, various and many approaches and models have been presented, the use of which increase the scientific and literary value of a work. Literary texts are always full of words, sentences and melodious constructions. One of the challenges of translators when translating such texts is to transfer the elements of the original text correctly and accurately in the translated text. Henri Meschonnic's poetics approach of artistic translation, which includes components such as (transparency and centripetalism, experimental application and theoretical application, and inter-poetics relations), is considered as a leading approach in providing translations in accordance with the criteria and frameworks of the original and target text. This research is based on the descriptive-analytical method and its purpose is to examine Ruhollah Rahimi's Persian translation of the novel "Under the Feet of Mothers " based on the aforementioned theory. The reason for choosing this novel and Rahimi's translation of it is to have the necessary linguistic capacities and capabilities to adapt and implement the components of Henri Meschonnic’s Poetics of Translating. In this research, the following two questions are answered:1- Which of the components of the Henri Meschonnic’s Poetics of Translating is more prominent in Rahimi's translation?2- What is the function of the components of the mentioned approach in transferring the text message?Literature ReviewThe subject of the present research has not been investigated in any article or thesis so far, but considerable theses and articles have been written with the focus of examining the translation of other novels based on the ideas put forward for translation, which are referred to below. Due to the fact that Antoine Berman has followed the views of people like Henri Meschonnic in presenting his theory, therefore, in this section, the works written based on Berman's theory are also mentioned:- Valiullah Esmaili (2016), in his dissertation entitled Translation and Structural Criticism of the Novel Kabartu wa Nasitu an Ansa by Buthaina Al-Issa, has translated and criticized the fictional elements of the said novel. Individual theory was not used in the translation of this novel, and the translator relied on theory and general knowledge to translate the text and then criticize it.- Ali Bashiri (2019), in the article Implementation of Antoine Berman's Theory of Deconstructive Trends in the Translation of a Novel from Persian to Arabic (a case study of two translations of Boof-e Koor), has examined the aforementioned translations based on Berman's theory. The result of the research shows that all the issues related to Antoine Berman's theory can be applied in the translation of this novel, except Glorification, and the reason for not achieving Glorification in the translation of this prose is that the type of this prose is a novel and it is of a modern type, and the goal of the author and as a result the translator of the novel is far from Glorification and the use of figures.- Saber Mohseni (2019), in the article Investigation of Rhythm in the Persian Translations of Christian Boben Case Study: Mahvash Ghavimi's translation of geai (Idiot of the neighborhood) and Isabelle Bruges", has investigated the rhythm in Mahvash Ghavimi's translations of Christian Boben's works based on the artistic rhythm component of Meschonnic. The analysis of the translation of the two stories of Ablah-e Mahaleh and Isabelle Bruges shows that although the translator sometimes deviated from the rhythm of the original text due to language differences or complying with spelling rules, he was successful in recreating the rhythm and signs of orality (oralité) of the text.- Rajaa Abu Ali and Behzad Esbaghi Giglo (2019), in the article Criticism and Analysis of Fatemeh Jafari’s Translation of Rabi Jaber's Novel Confessions (E’terafat) based on the theory of deconstructive trends of Antoine Berman, investigated the aforementioned translation based on seven components of the deconstructive components of Berman.The result of the research shows that, among the mentioned components, the expansion and the destruction of the rhythm of the text are among the most frequent factors of distortion of the text in the translation of Fatemeh Jafari, and these components also have an effect on ennoblement, and in some cases, we see an increase in the component of ennoblement in the translation.MethodologyBased on the descriptive-analytical method and using online and library sources, this research has investigated Rahimi's Farsi translation of the novel "Under the Feet of Mothers" based on the poetics perspective of Henri Meschonnic's translation.ConclusionA total of 24 samples were selected to examine the poetics components of Meschonnic’s translation, of which 5 samples were considered for the element of transparency and centripetalism, 11 for experimental application and theoretical application, and 8 for inter-poetics relations. With the investigations carried out on the translation text, the components of experimental application, theoretical application, and inter-poetics relations in Rahimi's translation are more frequent and have more manifestations.Considering that the mentioned novel has the characteristics of a literary text and has melodious folk and literary expressions and interpretations, and also despite the difference of cultural elements in the two languages, literal and direct translation cannot be appropriate to transfer meanings; therefore, the poetics approach of Meschonnic’s translation is a solution in this situation and helps to provide a suitable and at the same time accurate translation.In terms of transparency and centripetalism, the translator, taking into account the textual relationship between the original and target languages, as in the original text, used simple and unpretentious words and phrases in his translation, and his writing is full of rhythmic sentences with a pleasant pattern, which plays an important role in conveying the meaning and emotional load of the text.In the section of experimental application and theoretical application, the translator has used the components considered for theoretical application such as deletion, displacement, and additions, in order to ennoble and glorify his text, which can be a special type of ideology in translation, adopted by the translator to advance his goals in order to provide a literary translation.In the field of inter-poetics relations, it should be said that the translator has correctly used the tools needed to establish a precise and desirable relationship between the original text and the target text, and has responded to each of the prominent elements of the source text in the target text, and added to the integrity of the structure of the translated text. It can be said that the translator in this section has used literary devices such as metonymy and non-metonymy, which have the same aesthetic effect in the source and target text, well in his translation.The language of the translated text is embedded in accordance with the norms of Meschonnic’s poetics approach and the target text, and the translator has tried to show the cultural signs of the language and his ideological approach to the reader by providing an acceptable translation.It can also be said that the translator understood the meaning of the words, phrases, and idioms relatively and expressed the equivalent of each of them in the translation according to the context of the target text and the elements determined for the Meschonnic approach. Therefore, it can be said that the translator has fulfilled his mission of finding the elements of meaning generation in the original text and then recreating them in the translation to an acceptable extent. Although he has made mistakes in a few cases.